Effects of a topical botanically-enriched salve on cutaneous oxygenation. (1st February 2019) - Corroon, Jamie; Erlandsen, Andrew; Taylor, Jan; Hanes, Doug; Bradley, Ryan
Abstract : Objective: There is a medical need to evaluate new treatments that may improve wound healing. This study aimed to determine if Original Healing Salve (OHS, Puremedy, Inc.) a topical, botanically-enriched salve (BES), changes distal leg tissue oxygenation in people with type 2 diabetes. Method: A randomised, controlled, crossover, double-blinded clinical trial comparing changes in cutaneous oxygen delivery (mean TcPO2 ) on multiple sites of the lower extremity following application of a botanically-enriched topical salve, as compared with application of the salve's base in patients with type 2 diabetes. Subjects were recruited from the general population as a convenience sample. Results: A total of 16 participants were recruited. Analysis of the primary outcome demonstrated no statistically significant difference in TcPO2 at 30 minutes postapplication when comparing the BES to the base salve (BS) on the leg (–0.39±8.54mmHg; p=0.86). Analyses of secondary outcomes at 30 minutes postapplication indicated that mean TcPO2 was significantly higher than preapplication levels among subjects receiving both the BES (3.70±6.62mmHg; p=0.04) and BS on the leg (4.08±5.21mmHg; p=0.007). On the foot, mean TcPO2 at 30 minutes postapplication was higher in the BES compared with the BS, this difference was not significant (0.98±8.59mmHg; p=0.66). Mean TcPO2 was higher than preapplication levels among subjects receiving both the BES (1.21±7.70mmHg; p=0.54) and BS on the foot (2.19±7.27mmHg; p=0.25). These differences were non-significant. Conclusion: These findings support consideration of topical treatments containing botanical ingredients to increase cutaneous oxygen delivery in the lower extremity in patients with type 2 diabetes.